1985
DOI: 10.1093/oxfordjournals.aje.a114189
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Multiple Inference in Studies Designed to Generate Hypotheses

Abstract: Epidemiologic research often involves the simultaneous assessment of associations between many risk factors and several disease outcomes. In such situations, often designed to generate hypotheses, multiple univariate hypothesis-testing is not an appropriate basis for inference. The number of true positive associations in a collection of many associations can be estimated by comparing the observed distribution of p values for the positive associations to a theoretical uniform distribution, or to the observed di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(81 citation statements)
references
References 8 publications
2
79
0
Order By: Relevance
“…This is especially true when the study under consideration reports multiple between-group statistical comparisons, because multiple comparisons markedly inflate the actual Type I error rate and require a much more stringent statistical adjustment. [11][12][13][14][15] There is also concern about the Type II error rate of clinical trials (i.e., the so-called ␤ error), which reflects the likelihood of concluding incorrectly that a useful treatment is of no value. 16 For example, one recent trial 17 found that after 2 years of treatment, sustained disability progression was nonsignificantly reduced by 12%.…”
Section: Outcome Measures In Ms Clinical Trialsmentioning
confidence: 99%
“…This is especially true when the study under consideration reports multiple between-group statistical comparisons, because multiple comparisons markedly inflate the actual Type I error rate and require a much more stringent statistical adjustment. [11][12][13][14][15] There is also concern about the Type II error rate of clinical trials (i.e., the so-called ␤ error), which reflects the likelihood of concluding incorrectly that a useful treatment is of no value. 16 For example, one recent trial 17 found that after 2 years of treatment, sustained disability progression was nonsignificantly reduced by 12%.…”
Section: Outcome Measures In Ms Clinical Trialsmentioning
confidence: 99%
“…Some authors have argued, however, that the assumption of a universal null hypothesis is not tenable when many possible comparisons are carried out and, as a consequence, each association should be evaluated in relation to a separate null hypothesis, taking into account the validity of the study and prior evidences from laboratory and epidemiological research. [12][13][14][15][16][17][18][19][20][21][22][23] With reference to the excesses reported here, the available experimental and epidemiological data suggest that DDT may act as a multiple cancerogen 24 through different epigenetic mechanisms of action. [25][26][27] Limited evidence is available on the ability of dicofol to induce liver cancer in mouse.…”
Section: Discussionmentioning
confidence: 99%
“…For GWAS as well as nongenetic studies, the most powerful use of the data appears to be to analyze the data as a single combined data set with appropriate adjustment of statistical significance. 5,6 Confirmation of findings in independent data sets is desirable, and sometimes these are available to authors, but often this is not feasible and is done by others. Fortunately, false-positive reports are ultimately corrected by the scientific process, although more careful accounting for multiple comparisons and caution in the interpretation of findings can make this more efficient.…”
Section: Article See P 2456mentioning
confidence: 99%